2008
DOI: 10.1007/s11270-008-9827-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of As and Zn in Soils Affected by the Spill of a Pyrite Mine and Effectiveness of the Remediation Measures

Abstract: The concentrations of As and Zn in 100 georeferenced soils uniformly distributed throughout the area affected by the spill from the Aznalcóllar mine (April 1998) were analysed at three depths (0-10, 10-30, and 30-50 cm) and on four dates (autumn-winter 1998, 1999, 2001, and 2004). For an estimate of the geochemical background, 30 unaffected soils near the edge of the spill were also analysed at the same depths. The soils were contaminated before the spill and, the accident seriously increased the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Also, the existence of wells flooded by the spill where after repeated pumping and addition of neutralizing materials remain acidic indicates that an important volume of aquifer surrounding the wells was Although there are no data on the groundwater quality before 1998, the high levels of toxic elements found in the waters of the Agrio and Guadiamar rivers prior to the failure of the dam (Cabrera et al 1984;Cabrera et al 1987;Arambarri et al 1996), even higher than those found after the spill (Olías et al 2006), clearly show the existence of this previous contamination. This is also noted in other studies conducted on the soils (Kraus and Wiegand 2006;Simón et al 2009) and the river sediments (Martin et al 2000;Hudson-Edwards et al 2003;Turner et al 2008). …”
Section: Temporal Evolutionsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, the existence of wells flooded by the spill where after repeated pumping and addition of neutralizing materials remain acidic indicates that an important volume of aquifer surrounding the wells was Although there are no data on the groundwater quality before 1998, the high levels of toxic elements found in the waters of the Agrio and Guadiamar rivers prior to the failure of the dam (Cabrera et al 1984;Cabrera et al 1987;Arambarri et al 1996), even higher than those found after the spill (Olías et al 2006), clearly show the existence of this previous contamination. This is also noted in other studies conducted on the soils (Kraus and Wiegand 2006;Simón et al 2009) and the river sediments (Martin et al 2000;Hudson-Edwards et al 2003;Turner et al 2008). …”
Section: Temporal Evolutionsupporting
confidence: 83%
“…Iron-rich clayey materials were also added in some areas (Aguilar et al 2007), and the surface was plowed to mix more contaminated surface horizons with deeper layers and so to thin down toxic element levels (Galán et al 2002;Simón et al 2009). Toxic element levels in soils are still high in many areas (Kraus and Wiegand 2006;Alvarez-Ayuso et al 2008;Simón et al 2009).…”
Section: Remediation Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, immediately after the spill the Andalusian and Spanish authorities began to clean and restore the affected areas, undertaking preventive and mitigating measures [3], [4]. Nevertheless, low-level residual heavy metal contamination remained [9][13].…”
Section: Introductionmentioning
confidence: 99%
“…The final measurement was the stabilization of the soils by revegetation with native plants. A monitoring of the area in 2004 (6 years after the accident) revealed that although the remediation measurements lowered the As concentrations, the percentage of soils exceeding the maximum permitted level for agricultural soils was around 65% of the total affected soils, while around 30% of the soils had even doubled the maximum permitted of As (100 mg kg −1 ; Simón et al, 2009). In this chapter, we present a general overview of the time course of As content in soils during the remediation actions undertaken in the affected area.…”
Section: Introductionmentioning
confidence: 99%